2014
DOI: 10.1002/14651858.cd004121.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory agents to induce regression and prevent the progression of cervical intraepithelial neoplasia

Abstract: There are currently no convincing data to support a benefit for NSAIDs in the treatment of CIN (very low quality evidence according to GRADE criteria). Results from a large on-going randomised study of celecoxib are awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, the efficacy of anti‐inflammation therapies in inhibition of postoperative tumor progression remains unclear. For example, Elecoxib, a COX2‐specific inhibitor, did not significantly affect apoptosis in prostate, and breast cancer as well as cervical intraepithelial neoplasia 142,148,149 . Similarly, intraoperative use of a single dose of parecoxib, another NSAIDs drug, was not associated with decreased cancer recurrence after bladder cancer surgery 150 …”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…However, the efficacy of anti‐inflammation therapies in inhibition of postoperative tumor progression remains unclear. For example, Elecoxib, a COX2‐specific inhibitor, did not significantly affect apoptosis in prostate, and breast cancer as well as cervical intraepithelial neoplasia 142,148,149 . Similarly, intraoperative use of a single dose of parecoxib, another NSAIDs drug, was not associated with decreased cancer recurrence after bladder cancer surgery 150 …”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Human papilloma virus (HPV) infection of the cervical epithelium is well regarded as the main cause of cervical cancer [83], and a link between HPV E6 and E7 oncoproteins and COX-2 transcription has been established [84,85]. However, current data supporting a benefit for NSAIDs in the treatment of cervical intraepithelial neoplasia—the premalignant cervical lesion—are uncertain [86]. COX-1 up-regulation in cervical carcinoma was reported more than 10 years ago, and COX-1-dependent autocrine/paracrine regulation of COX-2, PGE 2 receptors, and angiogenic factors was demonstrated in vitro [87].…”
Section: Cox-1 Involvement In Neoplastic Diseasesmentioning
confidence: 99%
“…3 Several studies have suggested that some drugs can prevent CIN, but the clinical efficacy of such drugs remains controversial. 70,71 In recent years, studies have found that alprostadil can prevent CIN in patients undergoing CAG/PCI. 30…”
Section: Discussionmentioning
confidence: 99%